Revitalization of Chinatown Area on Semarang Street Based on The Distinctiveness Aspect - Sri Sasnita; D. Lindarto (International Journal of Mechanical, Industrial and Control Systems Engineering, 2025)
The Chinatown area on Semarang street is one of the places inhabited by a typical Chinese ethnic community. This area has a fairly dense activity. The image of Chinatown on Jalan Semarang has faded due to changing social, legal, and economic factors as well as social trends. As an area that plays a role in the growth of the city, there are unique elements that can revitalize the area. As an area that has a role in the city's development, there are unique elements that can revitalize the area. Distinctiveness is a person's opinion of a place different from others. Aspects of distinctiveness can increase the attractiveness of a place. A place will be easily recognizable if it has certain characteristics/uniqueness. The method used is qualitative with direct observation of the research area. The potential that exists in the area can be optimized. The revitalization of this area uses the distinctiveness theory which emphasizes the uniqueness of the local area, Kevin Lynch's theory is used to determine the existing landmarks in the area. The results obtained from the revitalization of the region as a place of trade and services by taking into account the aspects of distinctiveness.